2000
DOI: 10.1182/blood.v96.5.1685.h8001685_1685_1689
|View full text |Cite
|
Sign up to set email alerts
|

Effect of active prenatal management on pregnancy outcome in sickle cell disease in an African setting

Abstract: Sickle cell disease (SCD) is associated with an increased risk of medical complications during pregnancy. In sub-Saharan Africa, fetal and maternal mortality rates are particularly high. This study evaluated the effect of an active prenatal management program on pregnancy outcome in patients with SCD in an African setting. Pregnant women with SCD attending the National Teaching Hospital in Cotonou (The Republic of Benin, West Africa) were recruited before the 28th week of gestation. Management was based on pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 17 publications
6
44
0
1
Order By: Relevance
“…The case reports did not contain sufficient details on the methodology used to measure birthweight and were excluded 10–12 . Forty‐three studies described in 59 publications were reviewed (Table S1, see Supporting information) 13–72 . Most (56%, 24/43) were studies on the prevention of malaria by intermittent preventive treatment (IPTp) or chemoprophylaxis in the African subcontinent (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The case reports did not contain sufficient details on the methodology used to measure birthweight and were excluded 10–12 . Forty‐three studies described in 59 publications were reviewed (Table S1, see Supporting information) 13–72 . Most (56%, 24/43) were studies on the prevention of malaria by intermittent preventive treatment (IPTp) or chemoprophylaxis in the African subcontinent (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining publications did not mention whether twins, stillborn infants or those with congenital abnormalities were included in the analysis. Congenital abnormalities were reported in 15 publications 13,14,17,22,23,29,43,45,46,50,54,60–62,72 . Eight studies (18%) reported the length of the infant at birth and, of these, four reported IUGR 41,50,64,72 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the only other prospective cohort study describing improved management of pregnant women with SCD in Africa demonstrated that enhanced prenatal care specific for the region lowered maternal mortality from 26.7% to 1.8%, which was comparable to the 1.2% rate found in pregnant women without SCD in the same setting . Similar to our study, a multidisciplinary approach was used, but the study did not have a systematic evaluation of the deaths prior to the intervention, and was limited in describing reproducible protocols for management of SCD‐related complications, including vaso‐occlusive pain and acute chest syndrome …”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of formal evidence to guide clinical practice, we believe that pregnant women with SCD should be managed by a multidisciplinary team including haematologists and obstetricians with experience in high‐risk pregnancy . The optimal approach of managing pregnancy complicated by SCD, that results in improved maternal and fetal outcomes, is yet to be identified.…”
Section: Discussionmentioning
confidence: 99%